2014
DOI: 10.3389/fnhum.2014.00421
|View full text |Cite
|
Sign up to set email alerts
|

The readiness potential reflects intentional binding

Abstract: When a voluntary action is causally linked with a sensory outcome, the action and its consequent effect are perceived as being closer together in time. This effect is called intentional binding. Although many experiments were conducted on this phenomenon, the underlying neural mechanisms are not well understood. While intentional binding is specific to voluntary action, we presumed that preconscious brain activity (the readiness potential, RP), which occurs before an action is made, might play an important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 45 publications
1
52
5
Order By: Relevance
“…Finally, activity in the pre-supplementary motor area (preSMA) reflects motor intentions (Lau Rogers Haggard and Passingham 2004). The disruption of activity in the preSMA by repetitive trans-cranial magnetic stimulation (rTMS) has been found to lead to a reduction in outcome binding (Moore et al 2010) and the amplitude of the early readiness potential in the preSMA (associated with motor preparation) has been found to positively correlate with outcome binding (Jo et al 2014). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, activity in the pre-supplementary motor area (preSMA) reflects motor intentions (Lau Rogers Haggard and Passingham 2004). The disruption of activity in the preSMA by repetitive trans-cranial magnetic stimulation (rTMS) has been found to lead to a reduction in outcome binding (Moore et al 2010) and the amplitude of the early readiness potential in the preSMA (associated with motor preparation) has been found to positively correlate with outcome binding (Jo et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Jo et al (2014) reported a non-significant difference in intentional binding between mindfulness meditators and age-matched controls. However, Bayes factors can be employed to test evidence for the null hypothesis (Dienes 2014; Wagenmakers et al in press; Dienes 2016), and in fact a meta-analysis of the results of the two studies provides sensitive evidence for an increase in overall binding and outcome binding (see Supplementary materials).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations